Criminal Histories and Criminal Justice Processing of Drug Use Forecasting (DUF) Sample Members in Washington, DC, 1989-1991 - Carver, Jay ([Verlag nicht ermittelbar], 1994)
These data provide information on the relationship between arrestee drug tests and future criminality once other risk factors, such as prior criminal history, are accounted for. Also explored is whether the association between drug test results and future offending varies depending upon the attributes of individual offenders. The dataset contains information drawn from the Pretrial Services Agency (PSA) in Washington, DC, and the National Institute of Justice's Drug Use Forecasting (DUF) program. Data are available from each source for 1989 and 1990 with subsequent arrest data provided by PSA through August 1991. The 1989-1990 data supplied by PSA contain information on criminal history and drug test results taken at the time of arrest. Data provided from the DUF program include drug test results from a sample of persons arrested as well as information obtained from arrestee interviews on items such as family and work status. The combined data contain the arrestees' demographic characteristics, arrest and charge information, prior criminal history, and subsequent offending. Drugs tested for include cocaine, opiates, methadone, PCP, amphetamines, barbiturates, marijuana, methaqualone, Darvon, and Valium. In addition, self-reported information regarding an individual's use of and dependency on these drugs is supplied. Demographic information includes age, sex, income, and employment status. Due to changes in the DUF measurement instrument from 1989 to 1990, the variables contained in the two data files are not completely identical.